Treatment of PVC using an alternative low energy ion bombardment procedure - Rangel, Elidiane C. [UNESP]; dos Santos, Nazir M. [UNESP]; Bortoleto, Jose Roberto R. [UNESP]; Durrant, Steven F. [UNESP]; Schreiner, Wido H.; Honda, Roberto Yzumi [UNESP]; Rangel, Rita de Cassia C. [UNESP]; Cruz, Nilson C. [UNESP] (Elsevier B.V., 2011)
In many applications, polymers have progressively substituted traditional materials such as ceramics, glasses, and metals. Nevertheless, the use of polymeric materials is still limited by their surface properties. Frequently, selective modifications are necessary to suit the surface to a given application. Amongst the most common treatments, plasma immersion ion implantation (PIII) has attracted the attention of many researchers owing to its versatility and practicality. This method, however, requires a power supply to provide high voltage (tens of kV) negative pulses, with a controlled duty cycle, width and frequency. Owing to this, the implementation of PIII on the industrial scale can become economically inviable. In this work, an alternative plasma treatment that enables low energy ion bombardment without the need of a high voltage pulse generator is presented. To evaluate the efficiency of the treatment of polymers, polyvinylchloride, PVC, specimens were exposed to 5 Pa argon plasmas for 3600 s, at excitation powers, P, of between 10 and 125 W. Through contact angle and atomic force microscopy data, the influence of P on the wettability, surface free energy and roughness of the samples was studied. Surface chemical composition was measured by X-ray photoelectron spectroscopy, XPS. To evaluate the effect of aging under atmospheric conditions, contact angle and XPS measurements were performed one and 1334 days after the treatment. The plasma potential and ion density around the driven electrode were determined from Langmuir probe measurements while the self-bias potential was derived with the aid of an oscilloscope. From these data it was possible to estimate the mean energy of ions bombarding the PVC surface. Chlorine, carbon and oxygen contamination were detected on the surface of the as-received PVC. Upon exposure to the plasma, the proportion of chlorine was observed to decrease while that of oxygen increased. Consequently, the wettability and surface energy increased after the treatment but such modifications were not stable after aging: the contact angle increased for all the samples, modifying the initially hydrophilic surface into a highly hydrophobic one. Consistently, the surface composition also changed after aging: there was carbon enrichment due to further losses of oxygen and chlorine. Another relevant factor for the elevation of theta was the change in morphology induced by the treatment. At greater powers, the uniform matrix of the PVC was transformed into a columnar structure containing randomly distributed sharp pillars. Interpretation of such results is proposed in terms of the total energy deposited in the solid by ionic collisions. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: PVC; Ion bombardment; Plasma treatment; Wettability; Roughness